2010
DOI: 10.1007/s12291-010-0067-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxidative Stress and Antioxidant Status in Pregnant Anemic Women

Abstract: The present study was conducted to investigate the oxidant-antioxidant status in iron deficient pregnant anemic women. One hundred thirty pregnant women with iron deficiency anemia (IDA) were divided into three groups, namely mild (50), moderate (50) and severe (30) anemic along with pregnant healthy women as controls (50). The complete blood count, plasma lipid peroxidation products, enzymatic and non-enzymatic antioxidants were measured according to respective protocols. The levels of complete blood count, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
(23 reference statements)
2
12
0
Order By: Relevance
“…Similar to our results, increased parameters of oxidative stress, including MDA, in IDA have been reported in several studies [32][33][34][35]. Deokar et al [36] recently reported a significant increase in MDA in association with decreased antioxidants, SOD, vitamin C, vitamin E, and zinc in patients with IDA.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our results, increased parameters of oxidative stress, including MDA, in IDA have been reported in several studies [32][33][34][35]. Deokar et al [36] recently reported a significant increase in MDA in association with decreased antioxidants, SOD, vitamin C, vitamin E, and zinc in patients with IDA.…”
Section: Discussionsupporting
confidence: 92%
“…About 50% of all anaemic cases in pregnant women have been attributed to iron deficiency, because iron requirements are not readily met by dietary intake alone especially if iron bioavailability is poor in the pregnant women [19]. In addition, decreased red blood cell survival which is secondary to an increased susceptibility to oxidant damage has been observed in anaemia [20]. In this study we observed a proportion of 46.5% (522/1122) pregnant women to be anaemic.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, we found that in the control and mild group less iron is utilized instead of moderate and severe anemic patients, which leads to make available more free iron in the body that in term may eventually further enhance the oxidative stress levels in this group. There have been reports that lipid peroxidation was significantly accelerated in iron deficiency anemia [27][28]. It is well known that lipid peroxidation is a free radicalmediated phenomenon and that the lipids in RBCs are susceptible to peroxidation in the pathophysiology of iron deficiency anemia.…”
Section: Discussionmentioning
confidence: 99%